MRI displays involvement of the temporalis muscle and the deep temporal artery in patients with giant cell arteritis - Veldhoen, Simon; Klink, Thorsten; Geiger, Julia; Vaith, Peter; Glaser, Cornelia; Ness, Thomas; Duwendag, Dirk; Both, Marcus; Bley, Thorsten A. (European Radiology, 2014)
Purpose: To assess deep temporal artery and temporalis muscle involvement in patients with giant cell arteritis (GCA).
CRIS-Team Scopus Importer:2024-12-04
Keywords: Giant cell arteritis; Magnetic resonance imaging; Multicenter study; Temporal arteries; Temporalis muscle